The Effect of Halal-Labelled Food Awareness Towards Purchase Intention Among Urban Muslims (Study of Indonesian Students in Japan) - Yoga Fadhil Nurfajri (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
The objective of this research is to investigate the effect of halal-labeled food awareness towards purchase intention of Indonesian Muslim student in japan. Survey data obtained from 101 Indonesian students from all over Japan and was analyzed with descriptive and verification methods, whereas SMART-PLS was utilized for hypothesis testing. In this research, halal-labelled food purchase intention variable was derived from Alam & Sayuti (2011) and Bone et al (2007). The result showed that all of halal-labelled food awareness influence Indonesian Muslim student purchase intention, with perception toward halal certification variable was the most significant factors for halal-labelled food awareness and perceive behavioral control as the most significant factor which influence halal-labeled food purchase intention. The limitation in this researched is the data was obtained through online questionnaire and using snowball sampling method, this method may cause bias since author was unable to control the spreading of the questionnaire and people who did not meet the criteria to fill the questionnaire may filled it.Keywords: Halal awareness, halal-food , Islamic marketing, Japan, purchase intention.